Determination of the effectivity of composite members on structural behavior through different combinations - Kultur, Omer Faruk; Taskiran, Ahmet; Sayin, Baris (ELSEVIER, 2022)
The majority of the existing building stock has reinforced concrete load-bearing systems and relatively few buildings are steel-framed. On the other hand, composite frames are less preferred compared to these two types of structures. However, the effect of composite members (beams, columns, slabs) on the structural behavior of steel-framed buildings is still not fully known. Therefore, it is necessary to examine the structural behaviors of buildings with composite members. Therefore, the current paper examines the effectivity of composite members on structural systems. Three different building models with i. composite beams and composite col-umns, ii. steel beams and composite columns, and iii. composite beams and steel columns were numerically examined. The required profile types (size) for the structure models were determined by linear analysis considering the Eurocode 4 and AISC guides. Seismic performances of the structure models were then determined through nonlinear analyses. Finally, seismic performances of the three models were compared and the impact of composite members on the structural performance was determined. The results of this paper are believed to make a valuable contri-bution to the literature by determining the effect of composite members on the structural behavior of low-rise buildings through nonlinear analysis.
Keywords: Composite system; Structural behavior; Pushover analysis; FINITE-ELEMENT-ANALYSIS; SHEAR; Construction & Building Technology; Engineering; Materials Science